Reflection film
The reflective film structure with a metal oxide layer and inorganic blackening layer addresses adhesion and corrosion issues by minimizing residual stress and water vapor ingress, ensuring robust light leakage prevention.
Patent Information
- Application Number
- JP2023116342
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-24
AI Technical Summary
Existing reflective films suffer from insufficient adhesion of the black ink layer to the metal reflective layer due to compressive residual stress differences, leading to potential peeling and impaired light leakage prevention, while also being susceptible to metal corrosion.
A reflective film structure comprising a base film, a metal reflective layer, an inorganic blackening layer containing a metal compound and elemental metal, and a metal oxide layer, which is formed using a dry coating method to minimize residual stress differences and prevent water vapor infiltration.
The solution ensures strong adhesion of the blackening layer to the metal reflective layer, preventing peeling and corrosion, thereby maintaining effective light leakage prevention and enhancing durability.
Smart Images

Figure 2025013054000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a reflective film. [Background technology]
[0002] A liquid crystal display device comprises a liquid crystal panel having an image display surface, a backlight that emits light toward the rear surface of the panel, and a housing that houses these. The housing has a bezel portion as a frame around the image display surface. A reflective film is disposed on the inner wall surface of the bezel portion. This reflective film is used to prevent light from the backlight from leaking out from the bezel portion (prevention of light leakage). Such a reflective film is described, for example, in Patent Document 1 listed below. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2004-184443 A Summary of the Invention [Problem to be solved by the invention]
[0004] Patent Document 1 describes a reflective film having a white resin film, a metal reflective layer, and a black ink layer in this order in the thickness direction. According to Patent Document 1, the metal reflective layer is formed of a metal such as aluminum. The black ink layer is formed by printing black ink on the surface of the metal reflective layer on the white resin film. The black ink contains a resin binder and a black pigment. The preferred thickness of the black ink layer is 0.5 to 3 μm. From the viewpoint of preventing pinholes from being formed in the black ink layer, it is preferable that a plurality of black ink layers are laminated. In such a reflective film with a black ink layer, the above-mentioned light leakage is prevented by light reflection by the metal reflective layer and light blocking by the black ink layer.
[0005] However, in the reflective film of Patent Document 1, the adhesion of the black ink layer to the metal reflective layer is insufficient.
[0006] A black ink layer containing a resin binder is prone to compressive residual stress after the layer is formed. The compressive residual stress on the exposed surface side (the side opposite the metal reflective layer) of the black ink layer is greater than the compressive residual stress on the side fixed to the metal reflective layer. The thicker the black ink layer, the greater the difference in compressive residual stress on both sides. And the greater the difference in compressive residual stress on both sides of the black ink layer, the lower the adhesion of the black ink layer to the metal reflective layer. A black ink layer with insufficient adhesion is prone to peeling. Peeling of the black ink layer impairs the light leakage prevention function of the reflective film.
[0007] On the other hand, it is strongly required that the metal reflective layer of the reflective film is resistant to metal corrosion. This is to suppress deterioration of optical properties such as reflection properties in the reflective film due to metal corrosion. Such suppression of metal corrosion is also required for metal-containing layers other than the metal reflective layer in the reflective film.
[0008] The present invention provides a reflective film suitable for suppressing corrosion of a metal reflective layer and a blackened layer while ensuring adhesion of the blackened layer to the metal reflective layer. [Means for solving the problem]
[0009] The present invention [1] includes a reflective film comprising a base film, a metal reflective layer on the base film, an inorganic blackening layer on the metal reflective layer, the inorganic blackening layer containing a metal compound and an elemental metal, and a metal oxide layer on the inorganic blackening layer.
[0010] The present invention [2] includes the reflective film according to the above [1], wherein the metal reflective layer is an aluminum layer.
[0011] The present invention [3] includes the reflective film according to the above [1] or [2], wherein the elemental metal is copper.
[0012] The present invention [4] includes the reflective film according to any one of the above [1] to [3], wherein the metal oxide layer is an indium oxide layer.
[0013] The present invention [5] includes the reflective film according to any one of the above [1] to [4], wherein the metal oxide layer has a thickness of 5 nm or more.
[0014] The present invention [6] includes the reflective film according to any one of the above [1] to [5], further comprising a cured resin layer on the side of the metal oxide layer opposite to the inorganic blackening layer. Effect of the Invention
[0015] As described above, the reflective film of the present invention comprises a substrate film, a metal reflective layer on the substrate film, an inorganic blackening layer on the metal reflective layer, the inorganic blackening layer containing a metal compound and an elemental metal, and a metal oxide layer on the inorganic blackening layer. The inorganic blackening layer containing a metal compound and an elemental metal is suitable for forming a thin inorganic blackening layer by a dry coating method. The thinner the inorganic blackening layer is, the more the difference in compressive residual stress occurring on both sides in the thickness direction of the inorganic blackening layer after film formation can be reduced. Reducing such a difference in compressive residual stress of the inorganic blackening layer helps to ensure the adhesion of the inorganic blackening layer to the metal reflective layer. In addition, the reflective film comprises a metal oxide layer on the inorganic blackening layer, which is suitable for suppressing the infiltration of water vapor into the metal reflective layer and the inorganic blackening layer from the side opposite to the substrate film. By suppressing the infiltration of water vapor, corrosion such as galvanic corrosion is suppressed in the elemental metal in the inorganic blackening layer and the metal reflective layer. Therefore, the reflective film of the present invention is suitable for suppressing corrosion of the metal reflective layer and the inorganic blackening layer while ensuring adhesion of the inorganic blackening layer to the metal reflective layer. [Brief description of the drawings]
[0016] [Figure 1] 1 is a schematic cross-sectional view of one embodiment of a reflective film of the present invention. [Diagram 2]The present invention illustrates a method for producing the reflective film shown in Fig. 1. Fig. 2A illustrates a process for forming a metal reflective layer on a substrate film, Fig. 2B illustrates a process for forming an inorganic blackening layer on the metal reflective layer, Fig. 2C illustrates a process for forming a metal oxide layer on the inorganic blackening layer, and Fig. 2D illustrates a process for forming a cured resin layer on the metal oxide layer. [Diagram 3] 1 is a schematic cross-sectional view of a modified example of the reflective film of the present invention, which does not have a cured resin layer on a metal oxide layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] 1, a reflective film X according to one embodiment of the present invention includes a base film 10, a metal reflective layer 20, an inorganic blackening layer 30, a metal oxide layer 40, and a cured resin layer 50, in this order in a thickness direction H. The reflective film X extends in a direction (plane direction) perpendicular to the thickness direction H. The reflective film X is, for example, a reflective film that prevents light from a backlight of a liquid crystal display device from leaking out of a housing.
[0018] The base film 10 is a base material that ensures the strength of the reflective film X. The base film 10 has a first surface 11 and a second surface 12 opposite to the first surface 11. The base film 10 is, for example, a transparent resin film having flexibility. Examples of the material of the base film 10 include polyester resin, polyolefin resin, acrylic resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, polyimide resin, cellulose resin, and polystyrene resin. Examples of the polyester resin include polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate. Examples of the polyolefin resin include polyethylene, polypropylene, and cycloolefin polymer. Examples of the acrylic resin include polymethacrylate. From the viewpoints of transparency and strength, the material of the base film 10 is preferably polyester resin, and more preferably PET.
[0019] The substrate film 10 is preferably a white film from the viewpoint of ensuring significant light reflectivity of the substrate film 10. The white film is obtained, for example, by incorporating particles such as inorganic fillers that cause light scattering into a resin film. Examples of such particles include titanium oxide, calcium carbonate, barium sulfate, silica, and talc, and preferably at least one selected from the group consisting of titanium oxide and silica is used. These particles may be used alone or in combination of two or more kinds. The average particle size of the particles is, for example, 0.05 μm or more, preferably 0.1 μm or more, and, for example, 2 μm or less, preferably 1 μm or less. The content ratio of the particles in the substrate film 10 as a white film is, for example, 5% by mass or more, preferably 10% by mass or more, and, for example, 50% by mass or less, preferably 40% by mass or less.
[0020] The thickness of the base film 10 is preferably 20 μm or more, more preferably 30 μm or more, and even more preferably 35 μm or more, from the viewpoint of suppressing the infiltration of water vapor from the base film 10 side of the reflective film X into the metal reflective layer 20 and the inorganic blackening layer 30, and from the viewpoint of the strength of the reflective film X. The thickness of the base film 10 is preferably 300 μm or less, more preferably 200 μm or less, and even more preferably 150 μm or less, from the viewpoint of ensuring the handleability of the base film 10 in the roll-to-roll system.
[0021] The first surface 11 of the substrate film 10 may be subjected to a surface modification treatment from the viewpoint of ensuring adhesion of the metal reflective layer 20 to the substrate film 10. Examples of the surface modification treatment include corona treatment, plasma treatment, ozone treatment, primer treatment, glow treatment, and coupling agent treatment.
[0022] The metal reflective layer 20 is disposed on the first surface 11 of the base film 10. That is, the metal reflective layer 20 is in contact with the first surface 11.
[0023] The metal reflective layer 20 is formed from a metal having light reflectivity. Examples of metals forming the metal reflective layer 20 include aluminum (Al), silver (Ag), titanium (Ti), and alloys thereof. From the viewpoint of ensuring good light reflectivity of the metal reflective layer 20 for visible light, the metal of the metal reflective layer 20 is preferably aluminum or silver. That is, the metal reflective layer 20 is an aluminum layer or a silver layer.
[0024] The thickness of the metal reflective layer 20 is preferably 30 nm or more, more preferably 50 nm or more, and even more preferably 70 nm or more, from the viewpoint of ensuring the light reflectivity of the metal reflective layer 20 and the reflective film X. The thickness of the metal reflective layer 20 is preferably 500 nm or less, more preferably 300 nm or less, even more preferably 200 nm or less, still more preferably 150 nm or less, and even more preferably 120 nm or less, from the viewpoint of ensuring the adhesion of the metal reflective layer 20 to the base film 10.
[0025] The inorganic blackening layer 30 is disposed on the metal reflective layer 20. That is, the inorganic blackening layer 30 is in contact with the metal reflective layer 20.
[0026] The inorganic blackening layer 30 is an inorganic layer having high light absorption properties, and contains a metal compound and an elemental metal. The inorganic blackening layer 30 may contain a plurality of metal compounds. The inorganic blackening layer 30 may contain a plurality of elemental metals.
[0027] The metal compound is a compound of a metal and a nonmetal. Examples of the metal compound include metal oxides, metal nitrides, and metal carbides. The metal compound is preferably a metal oxide. Examples of the metal (first metal) in the metal compound include indium (In), copper (Cu), molybdenum (Mo), and iron (Fe). The first metal is preferably at least one selected from the group consisting of In, Cu, Mo, and Fe.
[0028] Examples of the elemental metal (second metal) include In, Cu, Mo, and Fe. The elemental metal is preferably at least one selected from the group consisting of In, Cu, Mo, and Fe. When the metal compound contains a plurality of elemental metals, the plurality of elemental metals preferably contain a metal different from the first metal. More preferably, the elemental metal is a metal other than the first metal.
[0029] The ratio of the first metal in the inorganic blackening layer 30 is preferably 10 atomic % or more, more preferably 20 atomic % or more, and also preferably 90 atomic % or less, more preferably 80 atomic % or less, from the viewpoint of realizing high light-shielding properties in the inorganic blackening layer 30. The ratio of the second metal in the inorganic blackening layer 30 is preferably 10 atomic % or more, more preferably 20 atomic % or more, and also preferably 90 atomic % or less, more preferably 80 atomic % or less, from the viewpoint of realizing high light-shielding properties in the inorganic blackening layer 30.
[0030] From the viewpoint of realizing high light-shielding properties in the inorganic blackening layer 30, the inorganic blackening layer 30 preferably contains a metal oxide as a metal compound and a simple metal other than the first metal, and more preferably contains indium oxide as a metal compound and copper as a simple metal. When the inorganic blackening layer 30 contains indium oxide and copper, the ratio of In in the inorganic blackening layer 30 is preferably 40 atomic % or more, more preferably 50 atomic % or more, and preferably 90 atomic % or less, more preferably 80 atomic % or less, from the viewpoint of realizing high light-shielding properties in the inorganic blackening layer 30. When the inorganic blackening layer 30 contains indium oxide and copper, the ratio of Cu in the inorganic blackening layer 30 is preferably 5 atomic % or more, more preferably 10 atomic % or more, and preferably 50 atomic % or less, more preferably 40 atomic % or less, from the viewpoint of realizing high light-shielding properties in the inorganic blackening layer 30.
[0031] The thickness of the inorganic blackening layer 30 is preferably 400 nm or less, more preferably 200 nm or less, even more preferably 150 nm or less, and even more preferably 110 nm or less, from the viewpoint of ensuring the adhesion of the inorganic blackening layer 30 to the undercoat (the metal reflective layer 20 in this embodiment). The thickness of the inorganic blackening layer 30 is preferably 5 nm or more, more preferably 10 nm or more, even more preferably 20 nm or more, even more preferably 30 nm or more, and particularly preferably 50 nm or more, from the viewpoint of ensuring the light-shielding properties of the inorganic blackening layer 30 and the reflective film X.
[0032] The luminous transmittance (Y value) of the inorganic blackening layer 30 at wavelengths of 380 nm to 780 nm in the CIE-XYZ color system is preferably 0.1% or less, more preferably 0.05% or less, and even more preferably 0.03% or less, from the viewpoint of ensuring the light-shielding properties of the inorganic blackening layer 30 and the reflective film X. The luminous transmittance is, for example, 0.001% or more, 0.005% or more, or 0.01% or more. The luminous transmittance can be measured, for example, by a spectrophotometer (product name "U-4100", manufactured by Hitachi High-Tech Science Corporation).
[0033] In this embodiment, the inorganic blackening layer 30 is a film formed by a dry coating method (dry coating film). Examples of the dry coating film include a sputtered film formed by a sputtering method and a vapor deposition film formed by a vapor deposition method, and the sputtered film is preferable.
[0034] The metal oxide layer 40 is disposed on the inorganic blackening layer 30. That is, the metal oxide layer 40 is in contact with the inorganic blackening layer 30.
[0035] Examples of metals in the metal oxide forming the metal oxide layer 40 include indium (In), zinc (Zn), tin (Sn), magnesium (Mg), nickel (Ni), cobalt (Co) and chromium (Cr). From the viewpoint of ensuring the water vapor barrier properties of the metal oxide layer 40, the metal in the metal oxide is preferably at least one selected from the group consisting of In, Zn, Sn, Mg, Ni, Co and Cr, and more preferably, the metal oxide layer 40 is indium tin oxide (ITO).
[0036] The thickness of the metal oxide layer 40 is preferably 5 nm or more, more preferably 8 nm or more, and even more preferably 10 nm or more, from the viewpoint of ensuring the water vapor barrier property of the metal oxide layer 40. The thickness of the metal oxide layer 40 is preferably 200 nm or less, more preferably 150 nm or less, and even more preferably 100 nm or less, from the viewpoint of ensuring the adhesion of the metal oxide layer 40 to the inorganic blackening layer 30.
[0037] In this embodiment, the cured resin layer 50 is disposed on the metal oxide layer 40. That is, in this embodiment, the cured resin layer 50 is in contact with the metal oxide layer 40. The cured resin layer 50 is a hard coat layer for making the reflective film X less susceptible to scratches.
[0038] The cured resin layer 50 is a cured product of a curable resin composition. The curable resin composition contains a curable resin. Examples of the curable resin include polyester resin, acrylic urethane resin, acrylic resin (excluding acrylic urethane resin), urethane resin (excluding acrylic urethane resin), amide resin, silicone resin, epoxy resin, and melamine resin. These curable resins may be used alone or in combination of two or more kinds. From the viewpoint of ensuring high hardness of the cured resin layer 50, at least one selected from the group consisting of acrylic urethane resin and acrylic resin is preferably used as the curable resin.
[0039] Examples of the curable resin include ultraviolet-curable resin and thermosetting resin. The ultraviolet-curable resin is preferred as the curable resin because it can be cured without high temperature heating and therefore helps improve the production efficiency of the reflective film X.
[0040] The curable resin composition may contain particles. Examples of the particles include inorganic oxide particles and organic particles. Examples of the material of the inorganic oxide particles include silica, alumina, titania, zirconia, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide. Examples of the material of the organic particles include polymethyl methacrylate, polystyrene, polyurethane, acrylic-styrene copolymer, benzoguanamine, melamine, and polycarbonate. The particles may be used alone or in combination of two or more kinds. As the particles, inorganic oxide particles are preferably used, and more preferably, at least one selected from silica particles and zirconia particles is used.
[0041] The average particle diameter (D50) of the particles is preferably 20 nm or more, more preferably 25 nm or more, and even more preferably 30 nm or more, from the viewpoint of ensuring the hardness of the cured resin layer 50. The average particle diameter (D50) of the particles is preferably 300 nm or less, and more preferably 100 nm or less, from the viewpoint of uniform dispersion of the particles in the cured resin layer 50. The average particle diameter (D50) of the particles is the median diameter in a volume-based particle size distribution (the particle diameter at which the volume cumulative frequency reaches 50% from the small diameter side), and is determined based on the particle size distribution obtained, for example, by a laser diffraction / scattering method.
[0042] The proportion of particles in the cured resin layer 50 is preferably 5% by mass or more, more preferably 8% by mass or more, and even more preferably 10% by mass or more, from the viewpoint of ensuring the hardness of the cured resin layer 50. The proportion of particles in the cured resin layer 50 is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less, from the viewpoint of uniform dispersion of the particles in the cured resin layer 50.
[0043] The thickness of the cured resin layer 50 is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 0.7 μm or more, from the viewpoint of exhibiting sufficient abrasion resistance in the cured resin layer 50. The thickness of the cured resin layer 50 is preferably 5 μm or less, more preferably 3 μm or less, even more preferably 2 μm or less, and even more preferably 1.5 μm or less, from the viewpoint of ensuring adhesion of the cured resin layer 50 to the metal oxide layer 40.
[0044] The luminous reflectance (Y value) of the reflective film X at a wavelength of 380 nm to 780 nm in the CIE-XYZ color system is preferably 80% or more, more preferably 82% or more, and even more preferably 85% or more, from the viewpoint of ensuring the light leakage prevention property described later for the reflective film X. The luminous reflectance is, for example, 90% or less, 95% or less, or 100% or less. The luminous reflectance (Y value) of the reflective film X is the reflectance of light irradiated onto the reflective film X from the substrate film 10 side.
[0045] The luminous transmittance (Y value) of the reflective film X at a wavelength of 380 nm to 780 nm in the CIE-XYZ color system is preferably 0.10% or less, more preferably 0.05% or less, and even more preferably 0.02% or less, from the viewpoint of ensuring the light leakage prevention property of the reflective film X described below. The luminous transmittance is, for example, 0.001% or more, 0.005% or more, or 0.01% or more. The luminous transmittance (Y value) of the reflective film X is the transmittance of light irradiated onto the reflective film X from the substrate film 10 side.
[0046] The reflective film X is produced by a roll-to-roll method, for example, as follows.
[0047] 2A, a metal reflective layer 20 is formed on the base film 10 (metal reflective layer forming step). Specifically, a metal is deposited on the first surface 11 of the base film 10 by a dry coating method to form the metal reflective layer 20. Examples of the dry coating method include a sputtering method and a vapor deposition method, and the sputtering method is preferred.
[0048] In the sputtering method, for example, a sputtering deposition apparatus capable of performing a film formation process by a roll-to-roll method is used. Specifically, in the sputtering method, a sputtering gas (inert gas) is introduced under vacuum conditions into a deposition chamber equipped with the sputtering deposition apparatus, while a negative voltage is applied to a target placed on a cathode in the deposition chamber. This generates a glow discharge to ionize gas atoms, and the gas ions collide with the target surface at high speed to eject target material from the target surface, and the ejected target material is deposited on the substrate film 10.
[0049] The material of the target placed on the cathode in the film formation chamber (i.e., the material of the metal reflective layer 20) is the metal described above with respect to the metal reflective layer 20. The air pressure in the film formation chamber during film formation by sputtering (sputter film formation) is, for example, 0.02 Pa or more, and, for example, 1 Pa or less. Examples of power sources for applying voltage to the target include DC power sources, AC power sources, MF power sources, and RF power sources (the same applies to the sputter film formation described later with respect to the inorganic blackening layer 30 and the metal oxide layer 40). The absolute value of the discharge voltage during sputter film formation is, for example, 50 V or more, and, for example, 500 V or less (the same applies to the sputter film formation described later with respect to the inorganic blackening layer 30 and the metal oxide layer 40).
[0050] 2B, an inorganic blackening layer 30 is formed on the metal reflective layer 20 (inorganic blackening layer forming step). Specifically, a material is deposited on the metal reflective layer 20 by a dry coating method to form the inorganic blackening layer 30. Examples of the dry coating method include a sputtering method and a vapor deposition method, and the sputtering method is preferred.
[0051] The material of the target placed on the cathode in the sputtering method (i.e., the material of the inorganic blackening layer 30) is, for example, a sintered body containing the metal compound and an elemental metal described above with respect to the inorganic blackening layer 30. The air pressure in the deposition chamber during sputter deposition of the inorganic blackening layer 30 is, for example, 0.02 Pa or more and, for example, 1 Pa or less.
[0052] According to the dry coating method, the inorganic blackening layer 30 can be formed thinner than the above-mentioned black ink layer formed containing a resin component. In such a thin inorganic blackening layer 30, the difference between the compressive residual stress on the side fixed to the metal reflective layer 20 and the compressive residual stress on the side opposite to the metal reflective layer 20 is small (the thinner the inorganic blackening layer 30, the smaller the difference in compressive residual stress on both sides). Furthermore, the small difference in compressive residual stress on both sides of the inorganic blackening layer 30 in the thickness direction H helps to ensure the adhesion of the inorganic blackening layer 30 to the metal reflective layer 20.
[0053] 2C, a metal oxide layer 40 is formed on the inorganic blackening layer 30 (metal oxide layer forming step). Specifically, a material is deposited on the inorganic blackening layer 30 by a dry coating method to form the metal oxide layer 40. Examples of the dry coating method include a sputtering method and a vapor deposition method, and the sputtering method is preferred.
[0054] The material of the target placed on the cathode in the sputtering method (i.e., the material of the metal oxide layer 40) is, for example, the sintered body of metal oxide described above with respect to the metal oxide layer 40. The air pressure in the deposition chamber during sputter deposition of the metal oxide layer 40 is, for example, 0.02 Pa or more and, for example, 1 Pa or less.
[0055] A series of processes from the metal reflective layer forming process to the metal oxide layer forming process are carried out on one pass line while the workpiece film is transported by a roll-to-roll method. During the process on one pass line, the workpiece film is never exposed to the atmosphere. After the formation of the metal reflective layer 20, the inorganic blackening layer 30 and the metal oxide layer 40 are sequentially formed on the metal reflective layer 20 without exposing the workpiece film to the atmosphere, which helps to ensure the adhesion of the inorganic blackening layer 30 and the metal oxide layer 40 to the metal reflective layer 20.
[0056] Next, as shown in FIG. 2D, a cured resin layer 50 is formed on the metal oxide layer 40 (cured resin layer forming step). The cured resin layer 50 can be formed by applying the above-mentioned curable resin composition onto the metal oxide layer 40 to form a coating film, and then curing the coating film. When the curable resin composition contains an ultraviolet-curable resin, the coating film is cured by ultraviolet irradiation. When the curable resin composition contains a thermosetting resin, the coating film is cured by heating.
[0057] In this manner, the reflective film X can be manufactured.
[0058] The reflective film X may not include the cured resin layer 50, as shown in Fig. 3. Such a reflective film X can be produced by not carrying out the above-mentioned cured resin layer forming step (Fig. 2D). In order to ensure the abrasion resistance of the reflective film X on the side opposite to the second surface 12, it is preferable that the reflective film X includes the cured resin layer 50.
[0059] As described above, the reflective film X includes a base film 10, a metal reflective layer 20 on the base film 10, an inorganic blackening layer 30 containing a metal compound and an elemental metal on the metal reflective layer 20, and a metal oxide layer 40 on the inorganic blackening layer 30. The inorganic blackening layer 30 containing a metal compound and an elemental metal is suitable for forming a thin inorganic blackening layer 30 by a dry coating method. The thinner the inorganic blackening layer 30 is, the more the difference in compressive residual stress occurring on both sides in the thickness direction of the inorganic blackening layer 30 after film formation can be reduced. Reducing such a difference in compressive residual stress of the inorganic blackening layer 30 helps ensure adhesion of the inorganic blackening layer 30 to the metal reflective layer 20.
[0060] Furthermore, the reflective film X having the metal oxide layer 40 on the inorganic blackening layer 30 is suitable for suppressing the infiltration of water vapor into the metal reflective layer 20 and the inorganic blackening layer 30 from the side opposite to the base film 10. By suppressing the infiltration of water vapor, corrosion such as galvanic corrosion is suppressed in the elemental metal in the inorganic blackening layer 30 and the metal reflective layer.
[0061] Therefore, the reflective film X is suitable for suppressing corrosion of the metal reflective layer 20 and the inorganic blackening layer 30 while ensuring adhesion of the inorganic blackening layer 30 to the metal reflective layer 20. Specifically, as will be shown in the examples described later, the higher the adhesion of the inorganic blackening layer 30 to the metal reflective layer 20, the more the inorganic blackening layer 30 is suppressed from peeling off, and the more the reflective film X can exhibit a good light leakage prevention function. EXAMPLES
[0062] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the examples. In addition, the specific numerical values of the blending amounts (contents), physical property values, parameters, etc. described below can be replaced with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than") of the blending amounts (contents), physical property values, parameters, etc. corresponding to those described in the above-mentioned "Form for carrying out the invention".
[0063] Example 1 First, a white polyethylene terephthalate (PET) film (product name: "Lumirror E20", thickness 38 μm, manufactured by Toray) was prepared as a base film.
[0064] Next, a metal reflective layer, an inorganic blackening layer, and a metal oxide layer were formed in this order on one side (first side) of the PET film by a sputtering method (sputtering film formation process). In this sputtering film formation process, a roll-to-roll sputtering film formation device (DC magnetron sputtering film formation device) was used. The device includes a payout chamber, a first film formation chamber, a second film formation chamber, a third film formation chamber, and a winding chamber. The payout chamber includes a payout roller. A roll of the above-mentioned base film was set on the payout roller as the work film. The winding chamber includes a winding roller capable of winding up the work film. In the first to third film formation chambers, the film formation process can be carried out while running the work film from the payout chamber to the winding chamber by a roll-to-roll method.
[0065] In the sputtering process, specifically, the first sputtering deposition in the first deposition chamber, the second sputtering deposition in the second deposition chamber, and the third sputtering deposition in the third deposition chamber were performed in sequence, and then the work film (base film / metal reflective layer / inorganic blackening layer / metal oxide layer) was wound around the winding roller in the winding chamber. In the first sputtering deposition, a 75 nm thick metal reflective layer (Al) was formed on the first surface of the PET film. In the subsequent second sputtering deposition, a 30 nm thick inorganic blackening layer (In2O3+Cu) was formed on the metal reflective layer. In the subsequent third sputtering deposition, a 20 nm thick metal oxide layer (ITO) was formed on the inorganic blackening layer. Specifically, each sputtering deposition is as follows.
[0066] In the first sputtering deposition, the sputtering deposition apparatus (the delivery chamber, the first to third deposition chambers, and the winding chamber) was evacuated to a vacuum, and then argon (Ar) was introduced as a sputtering gas into the first deposition chamber, and the pressure in the first deposition chamber was set to 0.3 to 0.4 Pa. An Al target (manufactured by Mitsui Metals) was used as the target. A DC power supply was used as the power supply for applying a voltage to the target. The deposition temperature (the temperature of the substrate film on which the Al layer is laminated) was set to 40°C. The type of power supply and the deposition temperature were the same in the second sputtering deposition and the third sputtering deposition.
[0067] In the second sputtering deposition, after the above-mentioned evacuation of the sputtering deposition apparatus, Ar was introduced as a sputtering gas into the second deposition chamber, and the pressure in the second deposition chamber was set to 0.3 to 0.4 Pa. In addition, a black inorganic target (product name "DIABLA12", a mixed target of indium oxide (In2O3) and copper (Cu), In ratio 67.3 (±3) mass%, manufactured by Mitsubishi Materials Corporation) was used as the target.
[0068] In the third sputtering deposition, after the above-mentioned evacuation of the sputtering deposition apparatus, Ar was introduced as a sputtering gas into the third deposition chamber, and the pressure in the third deposition chamber was set to 0.3 to 0.4 Pa. In addition, an ITO target (a composite oxide of indium oxide and tin oxide, tin oxide concentration 10% by mass, manufactured by Mitsui Metals) was used as the target.
[0069] Next, a curable resin composition was applied onto the metal oxide layer to form a coating film. The curable resin composition contains an ultraviolet-curable acrylic urethane resin (product name: AICA ITRON Z844, manufactured by AICA Kogyo Co., Ltd.) and methyl ethyl ketone as a solvent. Next, the coating film was dried and then cured by ultraviolet irradiation to form a hard coat (HC) layer having a thickness of 1 μm.
[0070] In this manner, the reflective film of Example 1 was produced. The reflective film of Example 1 has a laminated structure of a substrate film (PET, thickness 38 μm), a metal reflective layer (Al, thickness 75 nm), an inorganic blackening layer (In2O3+Cu, thickness 30 nm), a metal oxide layer (ITO, thickness 20 nm), and an HC layer (thickness 1 μm). In Example 1, the metal reflective layer, the inorganic blackening layer, the metal oxide layer, and the HC layer on the substrate film form a multilayer film.
[0071] Example 2 The reflective film of Example 2 was produced in the same manner as the reflective film of Example 1, except for the following: In the third sputtering deposition in the sputtering deposition process, the thickness of the metal oxide layer (ITO) formed was set to 10 nm.
[0072] Comparative Example 1 The reflective film of Comparative Example 1 was produced in the same manner as the reflective film of Example 1, except for the following. In the sputtering film-forming process, the third sputtering film-forming was not performed. That is, the metal oxide layer was not formed on the inorganic blackening layer. In Comparative Example 1, the metal reflective layer on the substrate film, the inorganic blackening layer, and the HC layer form a multilayer film.
[0073] Comparative Example 2 The reflective film of Comparative Example 2 was produced in the same manner as the reflective film of Example 1, except for the following. In the sputtering film-forming process, the first sputtering film-forming, the third sputtering film-forming, and the second sputtering film-forming were performed in this order. That is, a metal reflective layer, a metal oxide layer, and an inorganic blackening layer were formed in this order on the substrate film. In Comparative Example 2, the metal reflective layer, the metal oxide layer, the inorganic blackening layer, and the HC layer on the substrate film form a multilayer film.
[0074] Comparative Example 3 The reflective film of Comparative Example 3 was produced in the same manner as the reflective film of Example 1, except for the following. In the third sputtering deposition of the sputtering deposition process, an AlNx layer was formed instead of an ITO layer. In the third sputtering deposition, after the sputtering deposition apparatus was evacuated, Ar as a sputtering gas and nitrogen (N2) as a reactive gas were introduced into the third deposition chamber, and the pressure in the third deposition chamber was set to 0.3 to 0.4 Pa. The amount of N2 introduced into the third deposition chamber was set to 1 volume part per 15 volume parts of Ar introduced into the third deposition chamber (the flow rate ratio of Ar and N2 was 15:1). In addition, an Al target (manufactured by Mitsui Metals) was used as the target. In Comparative Example 3, the metal reflective layer, inorganic blackening layer, AlNx layer, and HC layer on the substrate film form a multilayer film.
[0075] <Thickness of each layer> The thickness of each layer (metal reflective layer, inorganic blackening layer, metal oxide layer, AlNx layer) in the reflective film of Examples 1 and 2 and Comparative Examples 1 to 3 was measured by observation with a field emission transmission electron microscope (FE-TEM). Specifically, first, a cross-sectional observation sample of each multilayer film of Examples 1 and 2 and Comparative Examples 1 to 3 was prepared by FIB microsampling. In the FIB microsampling method, an FIB device (product name "FB2200", manufactured by Hitachi) was used, and the acceleration voltage was set to 10 kV. Next, the cross-section of the multilayer film in the cross-sectional observation sample was observed by FE-TEM, and the thicknesses of the metal reflective layer, inorganic blackening layer, metal oxide layer (Examples 1 and 2, Comparative Example 2) and AlNx layer (Comparative Example 3) were measured in the observed image. In the observation, an FE-TEM device (product name "JEM-2800", manufactured by JEOL) was used, and the acceleration voltage was set to 200 kV. The measurement results are shown in Table 1.
[0076] <Luminous transmittance> The luminous transmittance of each of the reflective films of Examples 1 and 2 and Comparative Examples 1 to 3 was measured. Specifically, it is as follows.
[0077] First, a film piece for measurement (first film piece) was cut out from the reflective film. Next, the luminous transmittance of the first film piece was measured using a spectrophotometer (product name "U-4100", manufactured by Hitachi High-Tech Science Corporation). This transmittance is the luminous transmittance (Y value) of light with wavelengths of 380 nm to 780 nm transmitted through the first film piece in the CIE-XYZ color system. In this measurement, the first film piece was placed in the spectrophotometer so that light was incident on the base film side of the first film piece. The measurement results are shown in Table 1.
[0078] <Luminous reflectance> The luminous reflectance of each of the reflective films of Examples 1 and 2 and Comparative Examples 1 to 3 was measured. Specifically, the measurements were as follows.
[0079] First, the side of the reflective film opposite to the base film side was attached to a black acrylic plate via a specific adhesive. This resulted in a laminated film. Next, a film piece for measurement (second film piece) was cut out from the laminated film. Next, the luminous reflectance of the second film piece was measured using a spectrophotometer (product name "U-4100", manufactured by Hitachi High-Tech Science Corporation). This reflectance is the luminous reflectance (Y value) in the CIE-XYZ color system of irradiating light with a wavelength of 380 nm to 780 nm onto the second film piece. In this measurement, the second film piece was placed in the spectrophotometer so that light was irradiated from the base film side onto the second film piece. The measurement results are shown in Table 1.
[0080] Peel test For each of the reflective films of Examples 1 and 2 and Comparative Examples 1 to 3, the adhesion of the inorganic blackening layer was examined as follows.
[0081] First, a sample film was prepared for each reflective film. In preparing the sample film, a film piece (50 mm x 50 mm) was first cut out from the reflective film. Next, eleven parallel first cuts (1 mm apart) extending linearly in a first direction and eleven parallel second cuts (1 mm apart) extending linearly in a second direction perpendicular to the first direction were formed in the multilayer film on the base film in the film piece, and 100 grids were formed by the first and second cuts. In this way, a sample film was obtained. Each cut reached from the exposed surface of the multilayer film to the base film in the thickness direction.
[0082] Next, a peel test (grid peel test) was performed on each sample film in accordance with JIS K 5400. Specifically, a predetermined single-sided adhesive tape was attached to the multilayer film surface of the sample film so as to cover all 100 squares. Next, the adhesive tape was peeled off in a first direction. Then, the squares were observed after the adhesive tape was peeled off, and the presence or absence of peeling of the squares was confirmed. In each of the reflective films of Examples 1 and 2 and Comparative Examples 1 to 3, the number of squares that had at least a part peeled off was 0 (no peeling occurred in any squares).
[0083] Corrosion Test For each of the reflective films of Examples 1 and 2 and Comparative Examples 1 to 3, a first corrosion test was carried out as follows.
[0084] First, a sample film (210 mm x 297 mm) was cut out from the reflective film. Next, the sample film was irradiated with light of 2000 lux from the PET film side, and the multilayer film side of the sample film was observed to confirm that there were no defects with a maximum length of 500 μm or more in the surface direction (first confirmation step). The defects in this test are optical pinholes that allow light to pass through the multilayer film containing a highly light-reflective metal reflective layer and a highly light-shielding inorganic blackening layer, and are formed when local corrosion occurs in the metal component and the optical properties of the corroded area change. The observations were performed visually and, if necessary, with an optical microscope. Next, the sample film was left to stand for 72 hours in an environment with a temperature of 65°C and a relative humidity of 90% (standing step). Next, the sample film was irradiated with light of 2000 lux from the PET film side, and the multilayer film side of the sample film was observed to confirm the presence or absence of defects with a maximum length of 500 μm or more in the surface direction (second confirmation step). The observations were performed visually and, if necessary, with an optical microscope. The corrosion resistance of the reflective film was evaluated as "good" if no defects of 500 μm or more were found in the second confirmation step, and as "poor" if defects of 500 μm or more were found. The evaluation results are shown in Table 1.
[0085] The second corrosion test was carried out in the same manner as the first corrosion test, except that the standing time in the standing step was changed to 240 hours. The evaluation results of the second corrosion test are shown in Table 1. In addition, the third corrosion test was carried out in the same manner as the first corrosion test, except that the standing time in the standing step was changed to 500 hours. The evaluation results of the third corrosion test are also shown in Table 1.
[0086] [Table 1] [Explanation of symbols]
[0087] X Reflective Film H Thickness direction 10. Base film 11 Page 1 12 Side 2 20 Metal reflective layer 30 Inorganic blackening layer 40 Metal Oxide Layer 50 Cured resin layer
Claims
1. A base film; a metal reflective layer on the substrate film; an inorganic blackening layer on the metal reflective layer, the inorganic blackening layer comprising a metal compound and an elemental metal; a metal oxide layer on the inorganic blackening layer.
2. The reflective film of claim 1 , wherein the metallic reflective layer is an aluminum layer.
3. The reflective film of claim 1 , wherein the elemental metal is copper.
4. The reflective film of claim 1 , wherein the metal oxide layer is an indium oxide layer.
5. The reflective film of claim 1 , wherein the metal oxide layer has a thickness of 5 nm or more.
6. The reflective film according to claim 1 , further comprising a cured resin layer on the metal oxide layer opposite to the inorganic blackening layer.
Citation Information
Patent Citations
Reflective / light shielding self-adhesive tape
JP2004184443A